Autophagy in Health and Disease Potential Therapeutic Approaches (Stem Cell Biology and Regenerative Medicine,, 2018)
This timely volume explores the impact of autophagy in various human diseases, emphasizing the cell biological aspects and focusing on therapeutic approaches to these diseases. The chapters cover autophagy and its potential applications on diseases ranging from obesity, osteoarthritis, pulmonary fibrosis, and inflammation, through ALS, Parkinson's, retinal degeneration, breast cancer, alcoholic liver disease and more. The final chapters round out the book with a discussion of autophagy in drug discovery and 'bench to bedside'. Chapters are contributed by leading authorities and describe the general concepts of autophagy in health and disease, marrying cell biology and pharmacology and covering: studies derived from preclinical experiments, manufacturing considerations,and regulatory requirements pertaining to drug discovery and manufacturing and production. This volume will be useful for basic scientists as well as already practicing clinicians and advanced graduate students.